2011
DOI: 10.2176/nmc.51.701
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Morphometric Evaluation of Occipital Condyle for Occipitocervical Segmental Fixation

Abstract: Two recent novel techniques of occipital fixation are the occipitoatlantal (C0-C1) transarticular screw technique and the direct occipital condyle screw technique. The present study evaluated and compared the biomechanical stability of the direct occipital condyle screw and C0-C1 transarticular screw with the established method for craniocervical spine fixation using the midline occipital keel screw and C1 lateral mass screw. Morphometric evaluation of the occipital condyle and the hypoglossal canal was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…In our study the mean angle of occipital condyle to sagittal plane on the right was 30.52 degree and on the left side 29.6 degree but it was not significant. Kizilkanat et al [14] and Hong et al [3] found the angle of occipital condyle to sagittal plane as 31.5 and 33.5 degree respectively. Our finding goes hand in hand with Kizilkanat et al [14], Naderi et al [4].In the present study the angle of occipital condyle to the horizontal plane was measured on both sides.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study the mean angle of occipital condyle to sagittal plane on the right was 30.52 degree and on the left side 29.6 degree but it was not significant. Kizilkanat et al [14] and Hong et al [3] found the angle of occipital condyle to sagittal plane as 31.5 and 33.5 degree respectively. Our finding goes hand in hand with Kizilkanat et al [14], Naderi et al [4].In the present study the angle of occipital condyle to the horizontal plane was measured on both sides.…”
Section: Discussionmentioning
confidence: 96%
“…During this procedure the occipital condyle is resected fully or partially. In a study conducted by Hong et al [3], the occipital condye measurements were used in techniques such as transarticular and direct occipital screwing. Therefore a thorough knowledge of the measurements of occipital condyle is necessary for a The craniovertebral junction is an important landmark for the surgeons and radiologists to expose the posterior cranial fossa.…”
Section: Introductionmentioning
confidence: 99%
“…Classical techniques, such as occipital condyle screw[27] or occipital cervical plate,[1] are often sufficient for occipitocervical stabilization. However, these traditional fusion techniques fail due to screw “pull-out” from occiput,[4] screw fracture, and subaxial delayed instability with degenerative changes.…”
Section: Discussionmentioning
confidence: 99%
“…nerves, which can be caused by tips of other types of screws (3, 11,12). Further biomechanical studies on the stability of these types of occipital condyle-C1 lateral mass complex screws are needed.…”
Section: A B a B C D Ementioning
confidence: 99%